2020
DOI: 10.1101/2020.01.28.923284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melon ethylene-mediated transcriptome and methylome dynamics provide insights to volatile production

Abstract: 16During climacteric ripening large-scale transcriptional modifications are governed by ethylene. While 17 ripening-related chromatin modifications are also known to occur, a direct connection between these 18 factors has not been demonstrated. We characterized ethylene-mediated transcriptome modification, 19 genome methylation dynamics, and their relation to organoleptic modifications during fruit ripening in the 20 climacteric melon and an ethylene repressed line where the fruit-specific ACC oxidase 1 (ACO1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The melon flesh volatile profile has already been deeply studied, basically in commercial genotypes, but also including a few representatives of other horticultural groups [9,[11][12][13][14][15][16][17][18][19][20][21], and the comprehension of the pathways and genes involved in their biosynthesis is currently being prompted using genomic, transcriptomic and biochemical approaches and also segregating populations [22][23][24][25][26][27][28]. Recently, the flesh aroma profile of a melon core collection of 71 accessions representing the whole species diversity has been analyzed [5].…”
Section: Introductionmentioning
confidence: 99%
“…The melon flesh volatile profile has already been deeply studied, basically in commercial genotypes, but also including a few representatives of other horticultural groups [9,[11][12][13][14][15][16][17][18][19][20][21], and the comprehension of the pathways and genes involved in their biosynthesis is currently being prompted using genomic, transcriptomic and biochemical approaches and also segregating populations [22][23][24][25][26][27][28]. Recently, the flesh aroma profile of a melon core collection of 71 accessions representing the whole species diversity has been analyzed [5].…”
Section: Introductionmentioning
confidence: 99%
“…S3), suggesting that more than one DNA demethylase may be involved in this process. Moreover, a recent study showed hypomethylation of ethylene induced genes at 30 DAP in a climacteric variety, suggesting the important role of DNA demethylases during melon ripening (Feder et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies demonstrated that DNA methylation levels play an important role at the onset of fruit ripening in tomato (Zhong et al, 2013). Moreover, the DNA methylation dynamics in a climacteric and an ethylene repressed line have been recently studied in melon (Feder et al, 2020). Modulation of DNA methylation levels is governed by DNA methylases and demethylases.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MELO3C014437 (CmACO1), MELO3C009845 (CmCGS), MELO3C010776 (CmBCAT1), and MELO3C023371 (CmGKC) showed high expression levels in CM (Figure 1g). CmACO1, associated with ripening and ethylene biosynthesis [35][36][37], and CmCGS, a regulator of ethylene synthesis biochemical flux and SAM production [38], may contribute to reduced methylation in ACO1 antisense fruit. Additionally, ETH may control the synthesis of volatile aromatic and methyl-branched molecules through the relative expression of CmBCAT1, which catalyzes enhanced AT activity [39].…”
Section: Alternative Splicing Landscape Changes In Young and Mature S...mentioning
confidence: 99%